(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes in detail the concept of a mobile application that will be created to plan and manage physical education lessons for students and teachers of secondary schools, as well as to involve students in independent studies. The application allows students to independently study various physical exercises, sports techniques and theoretical knowledge, as well as the teacher can plan lesson topics, develop individual methods and simplify the process of evaluating results. In the course of the study, the effectiveness of this application and the possibilities of its use in physical education lessons were studied through theoretical, literary and practical experiments. The results confirm that innovative technologies play an important role in improving the quality of education and physical activity.